2023
DOI: 10.1101/2023.02.06.23285526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of coil placement approaches targeting dorsolateral prefrontal cortex in depressed adolescents receiving repetitive transcranial magnetic stimulation: an electric field modeling study

Abstract: Background: A promising treatment option for adolescents with treatment-resistant depression is high-frequency repetitive transcranial magnetic stimulation (rTMS) delivered to the left dorsolateral prefrontal cortex (L-DLPFC). Conventional coil placement strategies for rTMS in adults include the 5-cm rule, the Beam F3 method, and the magnetic resonance imaging (MRI) neuronavigation method. The purpose of this study was to compare the three targeting approaches to a computational E-field optimization coil place… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…E-field modeling is a method of accurately estimating how much non-invasive brain stimulation applied at the scalp reaches the cortical level using magnetic resonance imaging (MRI) scans, tissue segmentations/meshing, and tissue conductivity values ( Huang et al, 2017 ; Saturnino et al, 2019 ). As the magnitude of the E-field affects brain activity in a specific region or network, variability in the induced E-field can subsequently impact clinical response ( Suen et al, 2020 ; Caulfield et al, 2022b ; Zhang et al, 2022 ; Deng et al, 2023 ). Seminal studies in clinical TMS described how older individuals with larger scalp-to-cortex distances did not respond to treatments suggesting that the induced E-field magnitude is key to maximizing therapeutic response ( Kozel et al, 2000 ; Nahas et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…E-field modeling is a method of accurately estimating how much non-invasive brain stimulation applied at the scalp reaches the cortical level using magnetic resonance imaging (MRI) scans, tissue segmentations/meshing, and tissue conductivity values ( Huang et al, 2017 ; Saturnino et al, 2019 ). As the magnitude of the E-field affects brain activity in a specific region or network, variability in the induced E-field can subsequently impact clinical response ( Suen et al, 2020 ; Caulfield et al, 2022b ; Zhang et al, 2022 ; Deng et al, 2023 ). Seminal studies in clinical TMS described how older individuals with larger scalp-to-cortex distances did not respond to treatments suggesting that the induced E-field magnitude is key to maximizing therapeutic response ( Kozel et al, 2000 ; Nahas et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Zhang et al ( 27 ) of 12 patients receiving 3 weeks of left iTBS/right cTBS for depression found that the normal component of the electric field, not the tangential component or overall magnitude, was significantly correlated with antidepressant response. Finally, a comparison study was conducted by Deng et al ( 28 ) between four targeting methods (5 cm rule, Beam F3, MRI-guided, and electric field-optimization) using pilot data from ten adolescents receiving 30 daily sessions of 10 Hz rTMS. Significant correlation was observed between |E| in the DLPFC and antidepressant response in patients receiving a full course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…E-field modeling is a method of accurately estimating how much non-invasive brain stimulation applied at the scalp reaches the cortical level using magnetic resonance imaging (MRI) scans, tissue segmentations/meshing, and tissue conductivity values Saturnino et al, 2019). As the magnitude of the E-field affects brain activity in a specific region or network, variability in the induced E-field can subsequently impact clinical response (Suen et al, 2020;Caulfield et al, 2022b;Zhang et al, 2022;Deng et al, 2023). Seminal studies in clinical TMS described how older individuals with larger scalp-to-cortex distances did not respond to treatments suggesting that the induced E-field magnitude is key to maximizing therapeutic response (Kozel et al, 2000;Nahas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%